A randomized controlled study on expectant management of incomplete abortions caused by self medication - Kushwah, Beenu; Kushwah, Devendra Singh (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Medical method of termination of pregnancy is a very effective method when used as per recommended regimen and under proper supervision. Self-administration of these drugs has become a very common practice these days, resulting in incomplete abortion because of improper use. Traditionally surgical curettage has been the preferred mode of treatment for these cases but is associated with very high complication rates. Expectant management of incomplete abortion has been recently adopted as a better method of management of incomplete abortions worldwide. Present study compares expectant management with surgical curettage in cases of incomplete abortions caused by self medication. Methods: It was one-year prospective randomized controlled study. Total of 220 patients were recruited for the study out of which 103 were randomized to undergo expectant management while 117 to undergo surgical curettage. Results were compared using chi square test.. Results: Success rate of expectant and surgical management was found to be 82% and 95% respectively. Complication rate was found to be comparable in both the group while acceptability of expectant management was found to be much higher in expectant group. However, significantly more unplanned admissions and unplanned surgical curettage occurred after expectant management than surgical management. Conclusions: Expectant management is a safe and efficacious option in carefully selected cases. If used properly it can avoid complications associated with surgical management and therefore should be utilized whenever suitable.